Reversible occlusion (on-off) valves in shunted tumor patients - Hertle, Daniel; Tilgner, Johannes; Fruh, Karin; Keinert, Timo; Hertle, Anna M.; Unterberg, Andreas; Aschoff, Alfred (Neurosurgical review, 2011)
The first commercially produced adjustable valve for shunted hydrocephalus patients was introduced by H. Portnoy and R. Schulte in 1973. This valve is still in use and known as reversible occlusion or on-off valve. The reversible occlusion valve is mainly used in conjunction with an existing shunt in patients receiving intraventricular cytostatic therapy. The valve has a simple mechanical lock that is closed by external pressure application with a single finger. The study method is a retrospective clinical series of 15 patients undergoing a total of 16 valve implantations between 2003 and 2010 was carried out, and the valve was tested in vitro. We report a high incidence of accidental occlusions leading to a loss of consciousness in five patients (33.3%). We furthermore demonstrate in vitro that accidental occlusions can occur. The reversible occlusion valve is needed in shunted tumor patients receiving intrathecal administration of cytostatica. The mechanism works as long as no external pressure compresses the valve. However, head positions pose significant risks for unintentional occlusions. We stress the importance of: (1) a position near the midline avoiding the retroauricular or occipital regions, (2) a handling training for nurses and doctors, (3) instruction of patients and relatives, and (4) removal of the device after intrathecal cytostatic treatment.
Published online: 25 November 2010
Gesehen am 22.09.2022